Influence of elemental weight of human tissues estimated by ICCT software in absorbed dose calculation - Massicano, Felipe; Posssani, Rafael G.; Cintra, Felipe B.; Massicano, Adriana V. F.; Yoriyaz, Hélio (Revista Brasileira de Física Médica, 2015)
Therapeutic use of radiopharmaceuticals in Nuclear Medicine has been well established and presented good success rates against many forms of cancer. The biologic effects of radionuclide therapy are measured via a physical quantity, the absorbed dose, which is defined as per unit mass of tissue. Therefore, it is of great important an accurate dosimetry to assess the potential effects of treatment and to confirm or contradict the treatment predictions. The most common method used to estimate the absorbed dose at organ level was developed by Medical Internal Radiation Dose (MIRD) Committee, called MIRD system. However, this method does not have adequate patient data to obtain a dose estimate accurate in therapy. In recent years, internal radionuclide radiation dosimetry system evaluated spatial dose distribution. This system is based in Monte Carlo radiation transport codes with anatomical and functional information of the patient. The high accuracy is, at least in part, due to the Monte Carlo method allows human tissues to be characterized by elemental composition and mass density. Thus, a reliable estimation of human tissues (elemental composition and mass density) must be obtained. According to Schneider, Bortfield and Schlegel, the tissue parameters (mass densities (ρ) and elemental weights (ωi )) can be obtained using Hounsfield units provided from Computed Tomography (CT) images. Based on this, the Nuclear Engineer Center of IPEN developed the ICCT software (Image Converter Computed Tomography). It converts CT images in tissue parameters (mass densities (ρ) and elemental weights (ωi )). This work intended to verify if the estimate values by software ICCT of the tissue parameter and elemental weights (ωi ) are plausible to estimate the absorbed dose with reasonable accuracy